2018
DOI: 10.1192/bjp.2018.65
|View full text |Cite
|
Sign up to set email alerts
|

Ventromedial prefrontal cortex activity and pathological worry in generalised anxiety disorder

Abstract: Poor vmPFC safety-threat differentiation might characterise GAD, and its distinctive association with GAD worries suggests a neural-based qualitative difference between healthy and pathological worries.Declaration of interestNone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…GAD showed increased dALFF variability in the hippocampus and thalamus, limbic regions which are involved in emotion processing. Of note, emotional dysfunction is the most prominent feature of GAD (Mochcoyitch, da Rocha Freire, Garcia, & Nardi, 2014;Via et al, 2018), such as reduced capacity for engaging emotion-regulation brain networks when viewing and adjusting feelings toward positive and negative affective pictures (Blair et al, 2012), attenuated blood oxygen level-dependent response of the PFC and ACC to emotional expressions (Palm et al, 2011), and inability to adapt to emotional conflict (Etkin, Prater, Hoeft, Menon, & Schatzberg, 2010). The hippocampus is involved in the ventral affective neural systems and plays a critical role in mediating anxiety states in coordination with other limbic regions (Caliskan & Stork, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…GAD showed increased dALFF variability in the hippocampus and thalamus, limbic regions which are involved in emotion processing. Of note, emotional dysfunction is the most prominent feature of GAD (Mochcoyitch, da Rocha Freire, Garcia, & Nardi, 2014;Via et al, 2018), such as reduced capacity for engaging emotion-regulation brain networks when viewing and adjusting feelings toward positive and negative affective pictures (Blair et al, 2012), attenuated blood oxygen level-dependent response of the PFC and ACC to emotional expressions (Palm et al, 2011), and inability to adapt to emotional conflict (Etkin, Prater, Hoeft, Menon, & Schatzberg, 2010). The hippocampus is involved in the ventral affective neural systems and plays a critical role in mediating anxiety states in coordination with other limbic regions (Caliskan & Stork, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found alterations of specific fear-and extinction-relevant neural circuits in these diseases. For patients with generalized anxiety disorder (GAD), deficient vmPFC activity has been observed during fear-related task performance (Greenberg et al, 2013;Via et al, 2018). Individuals with PTSD show structural and functional deficits of various fear-related areas of the brain, including amygdala, PFC and hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…The dysfunction of top‐down control system in human brain, especially dorsolateral prefrontal regions including the left inferior frontal gyrus and right superior frontal gyrus, is associated with self‐reported ‘trait’ anxiety of individuals (Price et al, 2011). The ventromedial prefrontal cortex has been found to play a key role in the anxiety‐related processes (Clauss et al, 2016; Delli Pizzi et al, 2016; Via et al, 2018); investigations of activity in the prefrontal cortex may help establish the understanding of the attention network activity underlying anxious behaviour. Increased function of brain regions in the attentional network may enhance the attentional bias towards external erotic stimulation (Cheng et al, 2015; De Jong, 2009; Stoléru et al, 2012), which may contribute to rapid ejaculation.…”
Section: Introductionmentioning
confidence: 99%